A Comparative Study of Global Multi-Airport Systems: Differentiation and Development Approaches (Journal of Interdisciplinary Insights, 2024)
This study examines the strategies and best practices for differentiated passenger development within multi-airport systems. As the aviation industry continues to evolve, airports within multi-airport systems face increasing competition in attracting and serving diverse passenger segments. The analysis presented highlights key areas for differentiation, including service quality enhancement, price positioning, and specialized market segmentation. The study emphasizes the importance of collaborative efforts among airports, local authorities, airlines, and other stakeholders to optimize the collective capacity and passenger experience across the multi-airport network. The insights and recommendations provided serve as a valuable reference for airports seeking to navigate the complexities of multi-airport system development and deliver exceptional travel experiences for their customers.